Treating violence : a guide to risk management in mental health - Maden, Tony (Oxford University Press, 2007)
'Treating Violence' deals with the problem of violence by mental health patients. Studies have established that mental disorders lead to violence in a minority of sufferers. This book critically reviews risk assessment methods and summarises the evidence.